Analysis And Design Of Spread And Pile Foundations Using Geo5 - Naseer Baba, Dudekula; K. Nivedita, Smt. (Journal of Neonatal Surgery, 2025)
The safe and efficient design of foundation systems is a core focus in geotechnical engineering, particularly for structures subjected to varying soil conditions and load demands. This study presents a comprehensive analysis and design of both spread and pile foundations using GEO5, a robust geotechnical software suite that integrates soil mechanics theories with advanced numerical modelling. Spread foundations are analysed for shallow soil conditions with adequate bearing capacity, while pile foundations are considered where deeper, more stable strata are needed to support heavy loads. A real-time case study was undertaken to demonstrate the practical application of GEO5 in both scenarios. Site-specific soil data was obtained through borehole investigations and laboratory testing, including parameters such as unit weight, cohesion, angle of internal friction, and unconfined compressive strength. For spread foundations, the software evaluated bearing capacity, settlement behaviour, and safety against shear failure. For pile foundations, vertical and lateral load assessments, bearing capacity calculations, settlement predictions, and group effects like pile interaction were thoroughly examined. The analysis compared results from GEO5 with conventional empirical approaches, revealing improved accuracy and visualization in predicting foundation behaviour under complex loading and stratified soil profiles. All designs adhered to relevant IS codes, ensuring structural safety and serviceability. Optimization studies involving varying foundation dimensions were also conducted to identify cost-effective yet stable solutions. The findings confirm that GEO5 is a powerful tool for designing both shallow and deep foundations, streamlining the engineering process and enhancing the understanding of soil-structure interaction. Its utility extends from academic research to real-world engineering applications, especially in challenging geotechnical environments